Health economy innovation trends: a possible scenario for entrepreneurs - Aveni, Alessandro (Revista Coleta Científica, 2020)
The paper aim to analyze a scenario for health economics considering the attention that today is being given to the sector, because of the Covid-19 pandemic. Innovation on health economy has accelerated, however a central issue prevails for the entrepreneur: how to consider good health as an objective for entrepreneurship. A new approach to health economics is geared to the requirements of the patient more than the offer, even though public services are still the majority of the offer on the market in many countries. The result of the paper analysis is a table that summarizes eight future trends that can guide but strategic choices of entrepreneurs in this sector